2018
DOI: 10.1002/tee.22761
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of a turbulent‐like thermal plasma jet for nanopowder production

Abstract: This paper discusses theoretical models and numerical methods to simulate turbulent thermal plasma flow transporting a nanopowder. In addition to a thermal plasma flow model, a sophisticated model is described mathematically for the nanopowder's collective growth by homogeneous nucleation, heterogeneous condensation, and coagulation among nanoparticles, and also transport by convection, diffusion, and thermophoresis, simultaneously. Demonstrative simulations show clearly that a suitable numerical method with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 102 publications
0
30
0
Order By: Relevance
“…Excluding these additional factors, in sophisticated conditions, the fundamental mechanisms of turbulence transition of thermal plasma affecting nanopowders should be elucidated. Those mechanisms were explained in an earlier report [40] under conditions restricted to a 2D axisymmetric frame. However, a turbulent flow actually includes numerous vortices with 3D motions that directly affect nanopowder transport.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Excluding these additional factors, in sophisticated conditions, the fundamental mechanisms of turbulence transition of thermal plasma affecting nanopowders should be elucidated. Those mechanisms were explained in an earlier report [40] under conditions restricted to a 2D axisymmetric frame. However, a turbulent flow actually includes numerous vortices with 3D motions that directly affect nanopowder transport.…”
Section: Introductionmentioning
confidence: 79%
“…Elucidating the correlation between the dynamic behaviour of a plasma flow and the transient formation of a nanopowder distribution is indispensable. The issue has not been addressed to date using steady-state simulations or by experimentation, but it has recently been examined using time-dependent simulations restricted at a 2D axisymmetric frame for a direct-current nontransferred arc plasma jet [40] and a direct-current gas tungsten arc welding condition [41].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that a turbulent flow has an eddy diffusion effect on the temperature field and the vapor and nanoparticle distributions [17,28]. Although the present model accompanies no turbulence model, time-dependent eddy motions larger than the grid scale were expressed.…”
Section: Model Descriptionmentioning
confidence: 94%
“…They demonstrated that it obtained almost identical number density and mean diameter as the MOM with a complex description [34]. By extension of their model [33], a model that also expresses nanoparticle transport by convection and diffusion has been proposed as [18,21,28]…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation